Descriptive Analysis of Reported Adverse Events Associated with Amoxicillin/ Clavulanate potassium - Khan, Mohd F. (Asian Journal of Pharmaceutics (AJP), 2022)
Aim: Amoxicillin/clavulanate use leads to different adverse effects such as diarrhea, loose stools, skin rashes, nausea, and urticaria. The aim of the study was to describe the reported adverse events associated with the use of amoxicillin/ clavulanate potassium. Materials and Methods: The study included a descriptive analysis of the reports that were submitted to the FDA Adverse Event Reporting System (FAERS). Results: Between 1994 and 2022, 2203 reports about amoxicillin/clavulanate potassium adverse events were submitted to FAERS. The most reported adverse events were diarrhea (9.03%), pruritus (8.81%), hypersensitivity (7.67%), pyrexia (7.31%), rash (6.95%), dyspnea (5.99%), vomiting (5.54%), drug ineffective (5.08%), and nausea (4.31%).The present study showed also that amoxicillin/ clavulanate potassium use leads to several adverse events that could be serious events. Conclusion: It is important to increase the awareness of healthcare providers about the adverse events of broad-spectrum antibiotics such as amoxicillin/clavulanate potassium. The health-care providers should educate their patients about the adverse events of using amoxicillin/clavulanate potassium and about how to manage and how to report these events.